Penerapan Metode Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) Dalam Menentukan Bintara Polri Di Sumatera Utara - Soeb Aripin; Ria Zulkarnaen Harahap (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Selection of candidates for police officers is carried out by police institutions throughout Indonesia, with the aim of improving the quality of personnel. In this recruitment, the North Sumatran National Police prepare a large quota for the National Police NCO. The criteria sought in this recruitment are to meet the aspects of capability, potential ability, creativity, basic character and sincerity in carrying out their duties. The North Sumatra Regional Police is one of the government institutions that utilizes the development of technology and information, namely the creation of a system for the selection of non-commissioned officers. The problem that is often found in the North Sumatra Regional Police is that the selection of BINTARA so far is still considered less than optimal. The problem was because the examiners at the time of selection were still using the manual system. The manual system in question is that an examiner must first go to the office to take a list of the scores of the selection participants and then take it to the test location which is quite far from the SUMUT POLDA office. After that, the examiner must fill in the list of participants' scores at the test location and return it to the SUMUT POLDA office. The list of values will then be processed by the admin on duty in the office, then after processing, the results of the exam will be obtained. To determine how to select candidates for the National Police, the Decision Support System can be used. The research method used is the Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) method. The result of this study is to find out that Academic, Psychology, Health and Equality (Physical) have a very large influence in determining the selection of the National Police officer candidate in North Sumatra.